2013
DOI: 10.1111/jebm.12069
|View full text |Cite
|
Sign up to set email alerts
|

Quality of reporting clinical trials published in five leading Sri Lankan medical journals

Abstract: Reporting of several essential recommendations remained suboptimal. Education and training of trial methods and awareness of the CONSORT and TREND statements and more attention to the quality of reporting may improve matters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(143 reference statements)
0
1
0
Order By: Relevance
“…Several studies have assessed the overall methodological quality of scientific studies published in biomedical journals and concluded that the methodological quality of published research does not meet accepted standards. 2–7 While the overall assessment of the methodological quality of scientific research has been performed, the methodological quality of studies with positive versus negative findings in clinical medicine has not been compared.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have assessed the overall methodological quality of scientific studies published in biomedical journals and concluded that the methodological quality of published research does not meet accepted standards. 2–7 While the overall assessment of the methodological quality of scientific research has been performed, the methodological quality of studies with positive versus negative findings in clinical medicine has not been compared.…”
Section: Introductionmentioning
confidence: 99%